Trademark as a Measure of Innovation Performance in Kenya - Edmund Mallinguh; Zeman Zoltan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The article examines the determinants of innovation output proxied by trademark application, which is a form of intellectual property rights. The study employed data from the World bank on world development indicators for the period 1978-2017 inclusive of both years focusing on Kenya. The authors used a stepwise regression technique for data analysis. The findings suggest that youth unemployment (female) has an inverse relation while foreign direct investment and availability of domestic credit to the private sector from the financial industry have a direct relationship with innovation activities. However, the proportion of female to male workers (gender diversity) does not affect the number of trademark applications. The findings contribute to the existing literature on innovation performance as well as being useful to policymakers tasked with the regulation of entrepreneurial and innovative processes.